Do political events affect stock return volatility on Indonesian Stock Exchange - Vina Nurlita; Prima Naomi (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study has the purpose to examine the effect of political events on the volatility of stocks traded on the Indonesia Stock Exchange (IDX). Furthermore, this study also sees whether such political events also influence the shares that have direct links with the participants in presidential elections. The political event being examined was the Indonesian Presidential Election held in 2014. The researchers used the daily data on the shares of all companies listed on the Indonesia Stock Exchange (IDX) in 2014. The hypothesis testing were done using the GARCH (Generalized Auto Regressive Conditional Heteroscedasticity) estimation and its derivatives namely EGARCH (Exponential GARCH) and TARCH (Threshold GARCH). It was found that the 2014 Presidential Election asymmetrically affected stock return volatility on IDX and contrary to the leverage effect, which means that positive shocks (good news) have better influence than negative shocks (bad news). Out of all listed companies that have direct links with participants in the presidential election, 3 companies have their stock volatility affected by this Presidential Election; some with symmetric effect and some others with asymmetric effect.